ESTIMASI ANTROPOMETRI ANAK MELALUI VARIABEL BEBAS BODY MASS INDEX - , REZA PAHLEVI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Anthropometry is the field of ergonomics that specifically learn about the measurement of the human body to produce a product that is well adapted to the characteristics of the human body. Caused anthropometric measurement method that takes a long time and is less effective, so was born the idea of anthropometric measurements but using estimation methods. The purpose of this study was to determine the relationship of the independent variable Body Mass Index on child anthropometric parameters and anthropometric parameters estimation models build on the child's Body Mass Index independent variables. In this study, the authors use secondary data hereinafter called the data model development. The data amount to 150 children, consisting of 66 boys and 84 girls, aged 8 to 11 years. Then performed a statistical test phase normality test, test and test adequacy uniformity. Then proceed with phase correlation with anthropometric variables. Variables that have a correlation value (r) 0.4 to 1, then proceed to the modeling stage. Once the modeling is complete, then proceed to the stage of classical assumption test to check back so that the model can obtain the best estimator is not biased. Last performed model validation stage. This stage uses data validation to determine the extent of errors in the models. The results of this study resulted in 15 anthropometric parameters estimation models. 10 equations in boys and girls 5 equations. Then the model validation stage, the error rate equal to the boys resulted in an average value of MAPE 4.97%, whereas in girls produces an average value of 5.10% MAPE. Then the researchers tried to compare the average value of MAPE by other researchers. The result researchers have MAPE value smaller than the female sex but was greater in the male gender.